1999
DOI: 10.1211/0022357991772844
|View full text |Cite
|
Sign up to set email alerts
|

Vascular-selective Effect of Lercanidipine and other 1,4-Dihydropyridines in Isolated Rabbit Tissues

Abstract: The aim of this study was to characterize the in-vitro vasoselectivity of lercanidipine (in comparison with lacidipine, amlodipine, nitrendipine and felodipine) by evaluating its functional calcium antagonistic activity on rabbit vascular (aorta) and cardiac tissues (heart ventricle). Although incubation with all the compounds tested elicited a concentration-dependent relaxant effect on vascular tissue precontracted with KCl (80 mM), 50% relaxation was reached at different times for each concentration and drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
5

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 13 publications
0
21
0
5
Order By: Relevance
“…It is highly selective for vascular tissue and produces smooth muscle relaxation through competitive binding to L-type calcium channels. Compared to other CCBs, lercanidipine has many advantages, such as pronounced lipophilicity, excellent tolerance, short plasma half-life, few side effects (such as ankle edema or reflex tachycardia), and pronounced vascular selectivity (Angelico et al, 1999). Due to its excellent vascular selectivity and lipophilic status, lercanidipine is considered more suitable for hypertension patients with atherosclerosis than other drugs.…”
Section: Discussionmentioning
confidence: 99%
“…It is highly selective for vascular tissue and produces smooth muscle relaxation through competitive binding to L-type calcium channels. Compared to other CCBs, lercanidipine has many advantages, such as pronounced lipophilicity, excellent tolerance, short plasma half-life, few side effects (such as ankle edema or reflex tachycardia), and pronounced vascular selectivity (Angelico et al, 1999). Due to its excellent vascular selectivity and lipophilic status, lercanidipine is considered more suitable for hypertension patients with atherosclerosis than other drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Among factors responsible for heterogeneity among vessels, not only the specificity of the blocker and its voltage-dependency but also its tissue pharmacokinetics needs to be taken into account. For instance, Angelico et al (1999) have observed in isolated rabbit aorta stimulated by high KCl that 50% relaxation was reached at different times according to the CCB tested. At 10 nM concentration 50% relaxation was reached after 210 min with lercanidipine, 278 min with amlodipine, 135 min with lacidipine, 75 min with nitrendipine, and 70 min with felodipine.…”
Section: Tissue Selectivity Of Calcium Channel Blockersmentioning
confidence: 99%
“…Dihydropyridine Ca 2+ -channel blockers (CCBs) are effective at reducing blood pressure and improving cerebral vasculature (Frishman, 2002;Kuriyama et al, 1993). Lercanidipine, which is a long-acting and lipophilic dihydropyridine CCB, has been associated with desirable vasodilatory activity due to its vascular selectivity compared to other dihydropyridine derivatives (Angelico et al, 1999;Makarounas-Kirchmann et al, 2009) .…”
Section: Introductionmentioning
confidence: 99%